Turkey: In the midst of crisis, between liberal utopia and keynesian regulation - Üşenmez, Özgür (My University, 2017)
As Turkey’s growth numbers signalled negative news about the near future, possible economic remedies to solve an upcoming economic slowdown have been discussed. In this article by looking at the financial and banking sector performance of the country during 2001 local and 2008 global crisis, I tried to compare two mainstream strands of theory, i.e. liberal and Keynesian approaches to the economic crisis. It seems like the country has experienced a neo-liberal, unregulated financial episode until 2001 crisis, while in post-2001 period we have witnessed more regulatory and Keynesian financial remedies which were successful to save the country from more harmful effects of the Great Recession. Those Keynesian style regulations were mainly inspired from the effects of changes within the governing style of international financial institutions. But in the final section of the analysis, through pointing out the potential triggers for another economic crisis, this article argues that though Keynesian solutions are more logical and helpful in alleviating the symptoms of crisis, they could not make Turkey crisis-free. High current account deficits, persistent inflation, adamant unemployment and insufficient domestic production in the face of rising imports, all of these can be classified as the symptoms of the still crisis prone economic structure in the country. Then, other, more radical alternatives should be on the agenda for a better future.
Keywords: Keynesian,Neo-Liberal,Turkey,Crisis